Factors That Affect The Learning Of Religious Values In RA Bunayya Bin Baz Yogyakarta - Dea Khalika Siregar; ⁠lucky amanda; Jihan nur Azizah; Ammaturakhim Hasna; ⁠Naswa Zaini ihsan; Ririn Dwi Wiresti (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
The learning of religious values in early childhood at the Raudhatul Athfal (RA) level plays a very important role in shaping the character and religious foundation of students. This study aims to identify factors that can affect the effectiveness of religious value learning in RA Bunayya Bin Baz Bantul, Special Region of Yogyakarta. The subject of this study is the classroom teacher. The research method used is qualitative descriptive, with data collection techniques through observation, interviews, and documentation. The researcher also applies source triangulation to ensure the validity of the data, by comparing the results of observation, interview and documentation data to obtain complete and accurate data. The results of the research are applied to provide an overview of the aspects that affect the learning of religious values, both from internal factors such as teachers' abilities and learning approaches or methods, as well as external factors such as the school environment and the role of parents. This research is expected to be able to contribute to efforts to improve the quality of religious value education at the early childhood education level.